Glucose intake reduces craving in patients with alcohol use disorder depending on insulin response - Wetzel, Lea; Hoffmann, Sabine; Reinhard, Iris; Riegler, Alisa; Pourbaix, Madeleine; Ardern, Isabel; Link, Tobias; Vollstädt-Klein, Sabine; Lenz, Bernd; Kiefer, Falk; Koopmann, Anne; Bach, Patrick (European addiction research, 2025)
Introduction: There is evidence that the appetite-regulating hormone insulin plays an important role in alcohol use disorder (AUD), in the sense that there is a negative correlation between insulin and alcohol craving, meaning that an increase in insulin levels leads to a reduction in acute craving. This suggests a promising approach for the acute reduction of craving in the treatment of patients with AUD, which could be achieved via an actively induced short-term increase in insulin levels, e.g., by glucose administration, and which has not yet been investigated in the form of a randomized controlled trial. Another aspect that has not yet been investigated is the role of the insulin-responder-type of each individual, i.e., the time until the insulin peak is reached, in this relationship. Methods: The randomized, placebo-controlled, double-blind crossover study examined a glucose intake as acute treatment to reduce craving in 80 male and female patients with AUD. Dynamics in craving and insulin levels were assessed at 8 time points on each study visit before and after alcohol cue exposure, after treatment with glucose-respective placebo solution and during the subsequent observation phase. These changes were analyzed using linear mixed models. The insulin-responder-type (fast, normal, slow) of each person was taken into account, and possible interactions with the treatment were analyzed. Results: Linear mixed models revealed a significant interaction effect (F(2, 412.058) = 7.988, p < 0.001) between treatment and insulin-responder-type on craving, with lower craving values in the glucose compared to the placebo condition in the normal insulin-responder-type group (i.e., insulin peak after glucose intake within 30 to 60 min, difference in means = −0.805, p = 0.003, 95% CI: −1.428, −0.182). In the contrary, in the fast insulin-responder-type group craving values were higher in the glucose compared to the placebo condition (difference in means = 1.143, p = 0.011, 95% CI: 0.378, 1.907). Slow insulin-responders showed no differences in craving levels depending on the treatment condition (difference in means = −0.124, p = 0.694, 95% CI: −0.741, 0.493). No main effect was found in the linear mixed models for baseline-centered insulin levels (F(1, 395.337) = 2.328, p = 0.128). Conclusions: Glucose intake may reduce craving in individuals with AUD who show a normal insulin response. Further research should consider the different insulin-responder-types and peak times to better understand the underlying mechanisms of craving reduction with glucose administration in the context of insulin elevation.
Online veröffentlicht: 25. Juli 2025
Gesehen am 19.11.2025